Penataan Ruang dengan Pendekatan BCCT pada Pendidikan Anak Usia Dini - Nurul Novitasari (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2018)
This article discusses the arrangement of early childhood education institutions using the center and circle based approach or the Beyond Center and Circle Time (BCCT) approach. This approach focuses on children who in the learning process are centered in playing centers and when children are in a circle by using 4 types of scaf olding to support children's development: (1) playing environment footing; (2) footing before playing; (3) footing during playing; and (4) footing after playing. This approach is stimulated by children to actively engage in playing while learning in learning centers. Classrooms can be modified into small classes, called rooms or centers. Each center consists of one area of development. There are centers of worship, centers of natural materials, centers of main / art centers and centers of the role of micro, beam centers, preparation centers, centers of arts and creativity, centers of music and sports, and cooking centers. The teacher responsibles for 7-12 students only with moving classes every day from one center to another. To create a good classroom there are several factors that need to be considered: 1) room direction, 2) room size, 3) floor, 4) roof or ceiling, 5) wall management, 6) room color selection, 7) Attraction, 8) seating arrangement, 9) lighting, and 10) acoustic arrangement. This paper shows that there are many aspects that must be considered by managers of institutions that use the BCCT approach in arranging rooms so that they are comfortable and friendly and support teaching and learning activities for early childhood.